Paratopies romantiques - José-Luis Diaz (Contextes)
Through the example of French romanticism, this article aims at studying the importance of topology in the diverse writers’ scenographies that were then in force. The five romantic scenographies that will be examined are based on a topology of a distance, of a gap between the author and an imaginary norm. We will appeal to Dominique Maingueneau’s concept of ‘paratopia’. We would like to show that within each of the five romantic scenographies, the structural paratopic scheme is the link between the writer’s imaginary world and his discourse, considered at different levels: semiological device, ‘localization’ of the discourse, choice between oral and written speech, enunciation, ways of addressing the reader, generic and stylistical devices.